2019
DOI: 10.1097/txd.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Current Procurement Travel Practices, Accident Frequency, and Perceptions of Safety

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…More alarming data which emerged from the survey demonstrated that 80% of respondents had experienced a "near-miss" event while on a procurement trip, and 15% had been involved in at least one travel-related accident (27). These findings were subsequently supported by a study conducted by a separate team in 2019, in which 23% of surveyed transplant surgeons reported at least one travel accident with bodily injury (28). These risks may be due to the urgent nature of organ procurement, which often requires travel during adverse weather conditions and may result in poor compliance of safety precautions.…”
Section: Lung Procurement and Transportmentioning
confidence: 90%
“…More alarming data which emerged from the survey demonstrated that 80% of respondents had experienced a "near-miss" event while on a procurement trip, and 15% had been involved in at least one travel-related accident (27). These findings were subsequently supported by a study conducted by a separate team in 2019, in which 23% of surveyed transplant surgeons reported at least one travel accident with bodily injury (28). These risks may be due to the urgent nature of organ procurement, which often requires travel during adverse weather conditions and may result in poor compliance of safety precautions.…”
Section: Lung Procurement and Transportmentioning
confidence: 90%